2004
DOI: 10.1007/bf03347514
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c levels in non-diabetic patients with end-stage renal disease (ESRD) receiving hemodialysis

Abstract: Hemoglobin A1c (HbA1c) level represents an established tool to monitor glycemic control in diabetic patients, but the previous commonly used tests of HbA1c in patients with end-stage renal disease (ESRD) may not be reliable because of the presence of anemia, assay interference from uremia, and decreased red blood cell (RBC) life span. HbA1c level measured by turbidimetric immunoassay method is not affected by the above factors. We enrolled 40 non-diabetic ESRD patients receiving hemodialysis and 55 non-diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Three ESRD patients were diabetic, but were not frankly hyperglycaemic (individual HbA 1c values: 5.9 and 5.8%). As recently published [23], HbA 1c of the nondiabetic ESRD population was slightly elevated (n=11, 5.8± 0.3%), probably reflecting these patients' chronic anaemia, reduced erythrocyte life span and repetitive exposure to the high glucose level in the dialysate. In terms of renal function, as expected, ESRD patients had renal failure with elevated plasma creatinine (766±247 μmol/l, normal range: 45-110 μmol/l).…”
Section: Plasma Parameters Of Diabetic and Esrd Subjectssupporting
confidence: 57%
“…Three ESRD patients were diabetic, but were not frankly hyperglycaemic (individual HbA 1c values: 5.9 and 5.8%). As recently published [23], HbA 1c of the nondiabetic ESRD population was slightly elevated (n=11, 5.8± 0.3%), probably reflecting these patients' chronic anaemia, reduced erythrocyte life span and repetitive exposure to the high glucose level in the dialysate. In terms of renal function, as expected, ESRD patients had renal failure with elevated plasma creatinine (766±247 μmol/l, normal range: 45-110 μmol/l).…”
Section: Plasma Parameters Of Diabetic and Esrd Subjectssupporting
confidence: 57%
“…Furthermore, it has been shown that HbA 1c may be influenced by a host of factors independent of extracellular glucose levels including factors directly related to erythrocyte [15,16], environmental factors as diverse as chronic salicylate use [17], chronic dialysis [18], or micronutrient deficiency [19], and genetic factors including race or ethnicity [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent audit of these methods in our unit (42 patients with stage 5 chronic kidney disease: 22 HD, 12 peritoneal dialysis and 8 predialysis), mean HbA1c by HPLC was higher than that measured by immunoassay (IA) (mean HbA1c (HPLC) 6.8 ± 1.2% vs (IA) 6.4 ± 1.1%, mean difference 0.38%, 95% CI 0.46 to −0.29%, P < 0.0001 paired test, unpublished data). This is also seen when glycated haemoglobin is measured in non‐diabetic patients with ESRD 21 . Because non‐enzymatic protein glycation is a complex reaction that proceeds through early, intermediate and late stages and depends mainly on glucose concentration and protein half‐life, shortened red cell survival, anaemia, blood transfusion and recombinant erythropoietin use may all impact on the accuracy of the HbA1C measurement.…”
Section: Measurement Of Glycaemic Controlmentioning
confidence: 99%
“…This is also seen when glycated haemoglobin is measured in non-diabetic patients with ESRD. 21 Because non-enzymatic protein glycation is a complex reaction that proceeds through early, intermediate and late stages and depends mainly on glucose concentration and protein half-life, shortened red cell survival, anaemia, blood transfusion and recombinant erythropoietin use may all impact on the accuracy of the HbA1C measurement. To this end, a Japanese study has recently reported that glycated albumin may provide a significantly better measure of glycaemic control in diabetic HD patients compared with HbA1c because of the effects of anaemia and erythropoietin use.…”
Section: Measurement Of Glycaemic Controlmentioning
confidence: 99%